ANALISIS FAKTOR-FAKTOR PENGAMBILAN KEPUTUSAN PEMBELIAN KOSMETIK BERLABEL HALAL DI PEKALONGAN - Nur Kholidah; Muhammad Arifiyanto (STAI Syubbanul Wathon Magelang, 2021)
The halal lifestyle has recently been sweeping the world, including Indonesia. One of the halal products that are developing in Indonesia is cosmetic products. This phenomenon has an impact on the increasing purchase of halal cosmetics. With the increasing number of cosmetic companies emerging in Indonesia, the competition in the cosmetics business is getting tougher. To be able to win the competition so as not to be left behind by consumers, producers must follow the factors behind consumer purchasing decisions for a product. The objectives of this study were 1) to identify the characteristics of the respondents, and (2) to analyze the factors of purchasing decisions for cosmetic products labelled halal in Pekalongan. This research uses descriptive analysis, factor analysis and Net Promoter Score (NPS). The results of this study found that there are three groups of new factors in purchasing decisions for halal cosmetics, namely individual factors, self-concept and socio-culture. As many as 42% of respondents tend to recommend the cosmetic products they use to others.